Assessment of 35 children with abdominal tuberculosis - Kılıç, Ömer; Somer, Ayper; Hançerli Törün, Selda; Keser Emiroğlu, Melike; Salman, Nuran; Salman, Tansu; Çelik, Alaattin; Yekeler, Ensar; Uzun, Meltem (Turkish Journal of Gastroenterology, 2015)
Abstract Background/Aims: To contribute to the diagnosis and treatment of pediatric abdominal tuberculosis cases by assessing the clinical, laboratory, and radiological features of patients who presented at our clinic and were diagnosed with abdominal tuberculosis. Materials and Methods: Clinical, laboratory, and radiological features were reviewed retrospectively for 35 patients diagnosed with abdominal tuberculosis and followed up at the Pediatric Infectious Diseases Clinic between January 1987 and August 2012. Results: The study group included 16 female (45.7%) and 19 male (54.3%) patients with an age range of 6 months to 16 years (mean: 9.77±4.36 years). Twenty-nine patients were diagnosed with tuberculosis peritonitis, five patients with intestinal tuberculosis, and one patient with pelvic tuberculosis. The most common signs and symptoms were ascites, abdominal pain, abdominal distention, weight loss, and fever. Mean duration of the complaints was 109 days (range: 10 days to 3 years). Conclusion: Abdominal tuberculosis is a disease with an insidious course without disease-specific clinical and laboratory signs. When the disease is suspected, laparoscopy or laparotomy could be helpful in diagnosis. Employing ultrasound and computed tomography signs, abdominal tuberculosis should be included in differential diagnoses in regions with a high incidence of tuberculosis when there is abdominal pain, weight loss, ascites, history of contact with individuals with tuberculosis, and positive tuberculin skin test when patients have not been Bacillus Calmette Guerin BCG vaccinated.